Effect of Work Environment and Innovative Behavior on Teachers Work for Motivation State High School in Banda Aceh City - Said Ashlan; Samsul Bahri (research, training and philanthropy institution Natural Aceh, 2023)
The purpose of the research entitled Work Environment and Innovative Behavior on Teacher Work Motivation State Senior High School in Banda Aceh is to identify and analyze: (1) the influence of the work environment on teacher work motivation, and (2) the effect of innovative behavior on teacher work motivation. The subjects of the study were teachers of the Banda Aceh State Senior High School with a sample of 252 people. The sampling technique used is Proportional Random Sampling, which is proportional and random sampling. The data were analyzed using path analysis after calculating the correlation of all research variables in the form of a matrix. The results analysis of the effect exogenous variables on endogenous variables in each substructure obtained (1) The work environment has a positive effect on teacher work motivation of 0.524 (2) Innovative behavior has a positive effect on teacher work motivation of 0.309. The results of the study illustrate that (1) there is a direct positive effect of the work environment on teacher work motivation by 22.9%, and (2) there is a direct positive influence of innovative behavior on teacher work motivation of 17.6%. Based on the research results, it was found that the work environment and innovative behavior described have shown a positive and significant influence on teacher work motivation